CLINICAL MANAGEMENT AND DELIVERY OF A PREGNANT WOMAN WITH A UTERINE SCAR FROM SIX CESAREAN SECTIONS A METROPLASTY - Сергей Владимирович Баринов; Татьяна Владимировна Кадцына; Юлия Игоревна Тирская; Оксана Вячеславовна Лазарева; Юрий Игоревич Чуловский; Юлия Анатольевна Ковалева; Алена Игоревна Ермакова (Мать и дитя в Кузбассе)
The article describes the clinical observation of repeated surgical delivery in a woman who has a scar on the uterus after 6 cesarean sections and 3 metroplastics, and demonstrates the effectiveness of the combined method of surgical treatment with placenta accreta. The proposed technology of delivery of pregnant women with placenta accreta allows performing organ-preserving surgery with a decrease in the volume of blood loss. The original method of suturing the wound on the uterus allows forming a full-fledged scar on the uterus after a cesarean section and carrying a second pregnancy to term.